Mucoadhesive Microspheres of Atorvastatin Calcium: Rational Design, Evaluation and Enhancement of Bioavailability - Dewangan, Hitesh Kumar; Sharma, Arpana; Mishra, Ankit; Singour, Pradeep (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Atorvastatin Calcium (ATC) used for lowering the cholesterol levels in body. It is competitive inhibitor of hydroxyl methylglutaryl-coenzyme A (HMG-CoA) reductase, followed mevalonate pathway, which have low bioavailability and poor solubility. Present work focus on development of mucoadhesive microspheres of atorvastatin calcium, for improve the delayed transit, continuous longer period release and preclinical pharmacokinetic estimation in rabbit. Materials and Methods: Microsphere was prepared by emulsification method in which the independent variables (like polymer amount) were studied on critical quality attributes like entrapment efficiency, percentage yield and in-vitro release. Microspheres were characterized in terms of physicochemical parameters, micromeritic properties, FT-IR, DSC and mucoadhesive wash-off test and further, evaluated for their pharmacokinetics study in rabbits. Results: The designed microsphere exhibited an average size with smooth surface, negative zeta potential, maximum entrapment efficiency and sustained release. Microspheres fulfil the micromeritic properties and showed no any interaction between drug and polymer, confirmed by FT-IR and DSC. The in-vivo study demonstrated that the prepared microspheres are effective for colon targeted drug delivery system at longer duration. In pharmacokinetics study, relatively steady plasma drug concentrations were observed within after oral administration of drug. The AUC0-24h for formulation were significantly higher than that of pure drug (p<0.05). Conclusion: The pre-clinical oral bioavailability study of drug was increased as the relative availability values were high compared with pure drug and it showed delayed transit for longer period of time.
Keywords: Atorvastatin calcium; Mucoadhesive; Microspheres; Colon targeting; Bioavailability